MENENTUKAN POLINOMIAL MINIMAL ATAS GF p - A, Nunung; Irawanto, Bambang (MATEMATIKA, 2008)
Let is finite field with elements, denoted by . If be an extension field of and is the algebra element of , then , polynomial of of smallest degree such that called minimal polynomial of . If is primitive element, then whose called primitive polynomial, is the minimal polynomial of whose generate the elements of .The minimal polynomial of whose generate the elements of is the factor of , because the elements of are the solution of . So, if and are known we have . If we factoring it, will be obtained , the minimal polynomial of whose generate the elements of , where is some irreducible factor in of degree that contain a primitive element.